Human brain MRI at 500 MHz, scientific perspectives and technological challenges. (10th January 2017) - Le Bihan, Denis; Schild, Thierry
Abstract: The understanding of the human brain is one of the main scientific challenges of the 21st century. In the early 2000s the French Alternative Energies and Atomic Energy Commission launched a program to conceive and build a 'human brain explorer', the first human MRI scanner operating at 11.7 T. This scanner was envisioned to be part of the ambitious French–German project Iseult, bridging together industrial and academic partners to push the limits of molecular neuroimaging, from mouse to man, using ultra-high field MRI. In this article we provide a summary of the main neuroscience and medical targets of the Iseult project, mainly to acquire within timescales compatible with human tolerances images at a scale of 100 μ m at which everything remains to discover, and to create new approaches to develop new imaging biomarkers for specific neurological and psychiatric disorders. The system specifications, the technological challenges, in terms of magnet design, winding technology, cryogenics, quench protection, stability control, and the solutions which have been chosen to overcome them and build this outstanding instrument are provided. Lines of the research and development which will be necessary to fully exploit the potential of this and other UHF MRI scanners are also outlined.